2014
DOI: 10.1186/1471-2342-14-35
|View full text |Cite
|
Sign up to set email alerts
|

3D facial landmarks: Inter-operator variability of manual annotation

Abstract: BackgroundManual annotation of landmarks is a known source of variance, which exist in all fields of medical imaging, influencing the accuracy and interpretation of the results. However, the variability of human facial landmarks is only sparsely addressed in the current literature as opposed to e.g. the research fields of orthodontics and cephalometrics. We present a full facial 3D annotation procedure and a sparse set of manually annotated landmarks, in effort to reduce operator time and minimize the variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…13 These landmarks are relatively harder to determine visually, so require other methods such as palpation. 9 They are located on convex surfaces, and the operator should control their localization on the x-, y-, z-axes separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 These landmarks are relatively harder to determine visually, so require other methods such as palpation. 9 They are located on convex surfaces, and the operator should control their localization on the x-, y-, z-axes separately.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is not possible to palpate soft tissue points on 3-D photo-graphs, the repeatability of the measurements of such soft tissue points-especially pogonion and zygion-is open to discussion. 10 There are several studies on repeatability and reliability of 3-D soft tissue facial landmarks, [8][9][10][11][12][13] but conflicting results have been reported in these studies and no consensus has been reached. The aim of this study was to evaluate the intraexaminer repeatability and interexaminer reproducibility of soft tissue landmarks on 3-D stereophotogrammetric images.…”
mentioning
confidence: 99%
“…Relevant research concluded that the reproducibility of either measurement through manual anthropometry or that on 3D photography was unsatisfactory due to distortion of soft tissues and illegibility of anatomical structures. 19,20 In this study, in order to reduce errors in landmark identification, a CBCT-based dentofacial image was chosen as reference standard. 21 Five landmarks were digitized on the original digital dental model before the registration procedure.…”
Section: Discussionmentioning
confidence: 99%
“…However, manual landmarking is tedious to perform, difficult to standardize in practice, and prone to intra and inter-operator error 37 . Furthermore, sparse landmark configurations can only quantify form at defined landmarks that can be reliably identified and indicated by a human, and thus lack the resolution to fully characterize shape variation in between landmarks.…”
Section: Introductionmentioning
confidence: 99%